Byron—In-Between Sade, Lautréamont, and Foucault: Situating the Canon of “Evil” in the Nineteenth Century - Gonsalves, Joshua (Romanticism on the Net, 2006)
AbstractSade’s evil influence on Lord Byron haunts the margins of Byronic criticism. In this article I resuscitate the marginalized Marquis by tracing Byron’s influence on another son of Sade, the pseudo-Comte de Lautréamont. If Sade’s forever violated heroine Justine forms a hopelessly contradictory representation of Byron’s desire for in-nocence (or non-noxiousness) in the name of himself, his illicit affair with his half-sister Augusta, and his interminably complex rapport to other feminine, homosocial, and homosexual objects of desire, how does this clandestine influence estrange a user-friendly Byron from our comfortable stereotype of the poet as wholly different from that other aristocrat? An examination of Sade alongside Lautréamont’s Sadean strain in Maldoror replaces le mal at the core of Byron’s life-writing, thereby foregrounding his lordship’s attempt to evade the practical consequences of evil in his own work. Since Sade is also influential on contemporary criticism via poststructuralism or La Pensée 68, I work through the case of Foucault in order to show how this Sadean order of things is responsible for the tendency to evade confronting the ephemeral or merely literary status of “evil” in the nineteenth century (and beyond).